Nursing graduates transition to practice and factors affecting their readiness: a comparative study between Ha’il and Kuwait - Alshammari, Muna; Dayrit, Richard; Alobaidly, Alanoud M.; Hasan, Abdullah; Llego, Jordan; Albagawi, Bander Saad (Frontiers in Education, 2026)
IntroductionWork readiness refers to the preparedness level of graduates regarding their qualities and attributes for success in the workplace. Evaluating the preparedness of nursing graduates to practice is crucial to assist them during their transition from students to practicing professionals. This study assessed the preparedness of nursing graduates for practical hospital work in Kuwait and the Kingdom of Saudi Arabia, comparing both settings.MethodsThis cross-sectional study included participants who recently graduated from the University of Ha’il and started internships, along with nursing graduates from the College of Nursing in Kuwait. The Casey-Fink Graduate Nurse Experience Survey was utilized, and data were collected online using Google Forms. Data analysis was performed using the Statistical Package for Social Sciences version 26.ResultsOut of 287 respondents, 185 were from the University of Ha’il, and 102 were from the College of Nursing in Kuwait. Respondents from both institutions showed moderate levels of adaptation with mean (SD) scores of 3.01 (0.41) and 3.08 (0.40), respectively, with no significant difference [t(285) = −1.47, p = 0.14].DiscussionParticipants from both countries displayed moderate confidence in their patient care abilities, which decreased as the number of patients increased.